An experimental study of wet-cooking in organic vessels: implications for understanding the evolution of cooking technologies - Andy Langley; Andy Needham; Roland Kröger; Gabriel Cifuentes-Alcobendas; Mette Adegeest; Jess Cousen; Christopher Lance; Hannah Benton; Amy-Rose Mansbridge; Amanda Satchell; Lewis Tomlinson; Francesca Rockall-Birtles; et al. (Archaeological and Anthropological Sciences, 2023)
The ability to control and direct fire is a major evolutionary step in the human story. The development of aceramic cooking technologies is less well understood as they rarely survive in the archaeological record. However, inferential evidence such as fire-cracked rocks, earthen pits and heated bones suggest a variety of cooking methods were used prior to the invention of ceramics. Yet there is a paucity of experimental evidence testing the efficacy of perishable organic containers in tasks involving their use with heat. The study presents experimental results of organic containers and their use for heating water related to cooking. Containers were made from deer hide and pig stomach and water was heated using two different techniques: placing the container directly above a fire and placing hot stones into the container. The results suggest that different organic containers and heating types could attain and maintain a sub-boiling cooking temperature; however, not all could reach boiling point. It is argued that these sub-boiling methods may be as, or perhaps more, desirable than boiling, with potential implications for the development of vessels prior to the adoption of ceramics.